Analisis Lingkungan Hukum Bisnis Internasional Pada PT. Indofood Sukses Makmur Tbk. - Azzahra Tri Najla S (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
Indofood Sukses Makmur Tbk is one of the giant companies in Indonesia which produces various types of food and drinks such as instant noodles, snacks, flavorings and others located in Jakarta, Indonesia. The products produced by PT. Indofood Sukses Makmur Tbk has succeeded in spreading to the international market. The success of doing business in international markets certainly cannot be separated from international business ethics, one of which is the legal aspect. This research aims to analyze the extent to which companies comply with legal regulations in their product development approach. This research uses qualitative methods with descriptive data analysis. The research results show that PT. Indofood Sukses Makmur Tbk has consistently complied with the law in all its activities including product development strategies to maintain safety, quality, reputation and community loyalty.